Interaction between the GAGA factor and Mod(mdg4) proteins promotes insulator bypass in Drosophila. - Melnikova, L.; Juge, F.; Gruzdeva, N.; Mazur, A.; Cavalli, G.; Georgiev, P. (Proceedings of the National Academy of Sciences of the United States of America, 2004)
Chromatin insulators or boundaries are proposed to structure the chromatin fiber into functionally independent domains by promoting the formation of chromatin loops. These elements can block the communication between an enhancer and a gene when placed between them. Interestingly, it has been previously observed that two tandem copies of the Drosophila Su(Hw) insulator abolish this enhancer-blocking activity, presumably through pairing. This bypass effect has not been described with other insulators, however. In this report, we show that the insertion of binding sites for the GAGA factor (GAF) between an enhancer and the Su(Hw) insulator allows bypassing of the insulator. This bypass relies on the activity of both the GAF protein and the Mod(mdg4)-67.2 protein, a factor required for Su(Hw) insulator activity. We show that these two proteins interact in vitro and in vivo, providing molecular evidence of pairing between the GAF sites and the Su(Hw) insulator. Finally, we show that placing the Mcp boundary together with the Su(Hw) insulator between an enhancer and a promoter leads to bypass, again in a GAF- and Mod(mdg4)-dependent manner. Our data provide direct evidence that heterologous insulators can be bypassed by distal enhancers and identify the interaction between GAF and Mod(mdg4) as a possible means to regulate insulator activity.